1992
DOI: 10.1111/j.1600-0714.1992.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin‐A increases type I procollagen production and mRNA level in human gingival fibroblasts in vitro

Abstract: In order to study the pathogenesis of gingival overgrowth induced by the immunosuppressive drug cyclosporine-A (CyA), we investigated its effect on 3H thymidine incorporation and on collagen production and mRNA levels in fibroblast cultures obtained from normal human gingiva. At concentrations of 100, 500 and 1000 ng/ml, CyA did not modify thymidine incorporation after 24 and 72 h of incubation. However, after 24 h it significantly increased the level of 3H proline-containing proteins in the medium. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
3
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 20 publications
2
52
3
4
Order By: Relevance
“…Furthermore, these effects of CsA on human fibroblast proliferation may vary according to individual cell strains 9) . In contrast, other previous studies have suggested that CsA increases production of extracellular matrix, collagen and interleukin-6 but simultaneously decreases proliferation of human gingival fibroblast 10,11) . Nevertheless, it is apparent that CsA increases cell proliferation of human gingival fibroblast in vitro 12) .…”
Section: ⅰ Introductioncontrasting
confidence: 81%
“…Furthermore, these effects of CsA on human fibroblast proliferation may vary according to individual cell strains 9) . In contrast, other previous studies have suggested that CsA increases production of extracellular matrix, collagen and interleukin-6 but simultaneously decreases proliferation of human gingival fibroblast 10,11) . Nevertheless, it is apparent that CsA increases cell proliferation of human gingival fibroblast in vitro 12) .…”
Section: ⅰ Introductioncontrasting
confidence: 81%
“…13,14) In contrast, other reports showed that CsA has no effect on proliferation or an inhibitory effect in gingival fibroblasts. 16,23) Nevertheless, the present study showed that CsA promoted the proliferation of HGF over 0.1-10 mM in a dose-and time-dependent manner (Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
“…Many studies have shown increased transcriptional and translational levels of type I collagen in both tissue and fibroblast cultures derived from CyA-induced gingival overgrowth. [20][21][22] A growing body of evidence has connected myofibroblasts with the pathogenesis of several fibrotic processes, since they are the main source of the increased extracellular matrix deposition. 7,8,23,24 The regulatory cytokine TGF-β1 has been traditionally considered an inducer of the myofibroblast phenotypes both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%